A ribose-functionalized NAD+ with unexpected high activity and selectivity for protein poly-ADP-ribosylation - Xiao-Nan Zhang; Qinqin Cheng; Jingwen Chen; Albert T. Lam; Yanran Lu; Zhefu Dai; Hua Pei; Nikolai M. Evdokimov; Stan G. Louie; Yong Zhang (Nature Communications, 2019)
The study of NAD+ dependent ADP-ribosylation can be challenging. Here the authors report on the development of NAD+ analogues, using chemo-enzymatic methods, which can be used as probes to label the substrate proteins of poly-ADP-ribose polymerase.